2008
DOI: 10.1038/nature07596
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of the nanoscale dynamics of membrane lipids in a living cell

Abstract: Cholesterol-mediated lipid interactions are thought to have a functional role in many membrane-associated processes such as signalling events. Although several experiments indicate their existence, lipid nanodomains ('rafts') remain controversial owing to the lack of suitable detection techniques in living cells. The controversy is reflected in their putative size of 5-200 nm, spanning the range between the extent of a protein complex and the resolution limit of optical microscopy. Here we demonstrate the abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

68
1,435
5
11

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 1,416 publications
(1,557 citation statements)
references
References 32 publications
(37 reference statements)
68
1,435
5
11
Order By: Relevance
“…However, this concept was revised in the last 10-15 years and present concepts indicate the existence of distinct membrane domains [32, 33]. Sphingolipids interact with each other and with cholesterol molecules via hydrophilic interactions between the sphingolipid headgroups and the hydroxy group in the cholesterol molecule, respectively, and via hydrophobic van der Waal interactions between ceramide moieties and the sterol ring system [32-35]. The tight interactions of sphingolipids and cholesterol were suggested to promote the transition of membrane lipids into a liquid ordered status and the formation of very small distinct domains in the cell membrane, named rafts [32].…”
Section: Ceramidementioning
confidence: 99%
See 2 more Smart Citations
“…However, this concept was revised in the last 10-15 years and present concepts indicate the existence of distinct membrane domains [32, 33]. Sphingolipids interact with each other and with cholesterol molecules via hydrophilic interactions between the sphingolipid headgroups and the hydroxy group in the cholesterol molecule, respectively, and via hydrophobic van der Waal interactions between ceramide moieties and the sterol ring system [32-35]. The tight interactions of sphingolipids and cholesterol were suggested to promote the transition of membrane lipids into a liquid ordered status and the formation of very small distinct domains in the cell membrane, named rafts [32].…”
Section: Ceramidementioning
confidence: 99%
“…The tight interactions of sphingolipids and cholesterol were suggested to promote the transition of membrane lipids into a liquid ordered status and the formation of very small distinct domains in the cell membrane, named rafts [32]. Rafts are proposed to be very small membrane domains enriched in sphingolipids and cholesterol that spontaneously separate from other phospholipids in the cell membrane [32-35]. Recent microscopy studies demonstrated rafts in cells and indicated a size of approximately 20 nm [35].…”
Section: Ceramidementioning
confidence: 99%
See 1 more Smart Citation
“…The main application of STED has been structural imaging, but the reduction of the excitation volume results in a decreased number of fluorophores diffusing through that volume, which is advantageous for the investigation of molecular mobility and interactions by fluorescence correlation spectroscopy (FCS) [17][18][19][20]. FCS is a technique that allows the diffusion coefficient of a molecule to be determined from the analysis of the fluctuations of its fluorescence emission as it traverses a known volume: The lower the number of fluorophores within the focal volume, the more accurate the measurements.…”
Section: Stedmentioning
confidence: 99%
“…The combination of STED and FCS has allowed the study of the nanoscale dynamics of membrane lipids in a cell, showing that sphingolipids were transiently trapped in cholesterolmediated molecular complexes of sizes below 20 nm, whereas phosphoglycerolipids were not [18]. STED-FCS has also revealed a lipid-protein transient bonding that is dependent on the interacting species and is different from that responsible for forming cholesterol-dependent, liquid-ordered domains in model membranes [20].…”
Section: Chromosome Organisationmentioning
confidence: 99%